(untitled) (Canadian Hematology Today, 2025)
The last decade has witnessed significant progress in the clinical management of patients with newly diagnosed primary central nervous system (CNS) diffuse large B-cell lymphoma (PCNS-DLBCL, hereafter referred to as PCNSL). Data from several clinical trials have demonstrated the potential for long-term remission in a proportion of patients, particularly those eligible for intensive multi-agent chemotherapy approaches. High-dose methotrexate (HD‑MTX)‑based induction regimens remain standard-of-care globally for both younger and older patients with newly diagnosed PCNSL. However, with clinical trial data demonstrating the efficacy of multiple regimens (differing in partner chemotherapy agents, hematological toxicity, and MTX dose density), but with few randomized comparisons, the optimal induction regimen remains unclear. Consolidation therapy is key to survival outcomes in PCNSL. Thiotepa-based autologous stem cell transplantation (TT-ASCT) has been widely adopted as the consolidation therapy of choice for patients ≤70 years. However, it is increasingly recognized that appropriately selected patients older than 70 years can also benefit from TT-ASCT consolidation. In parallel, declining rates of whole-brain radiotherapy (WBRT) have been observed due to significant risk of neurotoxicity, particularly in patients aged ≥60 years. This review summarises the contemporary clinical management of patients with newly diagnosed PCNSL. We focus on key diagnostic considerations, the landscape of evidence-based first-line treatments, and practical guidance for treatment selection and delivery. We also briefly discuss specific scenarios, including human immunodeficiency virus (HIV)-associated PCNSL and vitreoretinal involvement in the context of PCNSL.